2020
DOI: 10.3390/su12187470
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Tools for Tourism and Cultural Tourism Impact Assessment

Abstract: The importance of data and evidence has increased considerably in policy planning, implementation, and evaluation. There is unprecedented availability of open and big data, and there are rapid developments in intelligence gathering and the application of analytical tools. While cultural heritage holds many tangible and intangible values for local communities and society in general, there is a knowledge gap regarding suitable methods and data sources to measure the impacts and develop data-driven policies of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 82 publications
0
22
0
1
Order By: Relevance
“…The RSSI value is processed by using the Kalman filter to filter out the abrupt data in the measurement value and eliminate the noise interference in the system itself and in the measurement process. After processing, the system error is reduced and the fluctuation of the RSSI data value is reduced [14], which lays a good foundation for the next numerical optimization processing.…”
Section: Principle Of Algorithmicmentioning
confidence: 99%
“…The RSSI value is processed by using the Kalman filter to filter out the abrupt data in the measurement value and eliminate the noise interference in the system itself and in the measurement process. After processing, the system error is reduced and the fluctuation of the RSSI data value is reduced [14], which lays a good foundation for the next numerical optimization processing.…”
Section: Principle Of Algorithmicmentioning
confidence: 99%
“…Next to social media, mobile positioning data (MPD) increasingly tends to complement conventional data sources in tourism studies and destination management, as these data are becoming crucial to how a destination utilizes its resources [9,29]. Passive mobile-cell information is generated each time a mobile phone communicates with a network (i.e., by calling, sending messages, or using cell data).…”
Section: The Use Of Social Media and Mobile Positioning Data In Tourism Research: A Literature Reviewmentioning
confidence: 99%
“…Using mobile positioning data, Nilbe et al [45] were able to detect differences in distances travelled by foreign visitors to events and regular (non-event) visitors in Estonia, while Raun et al [40] identified tourist destinations based on visitor flows. There has been a lot of technological advancement in the field [46][47][48][49][50][51], and there are already countries in the world (Estonia and Indonesia) where MPD is used to produce national tourism statistics [9].…”
Section: The Use Of Social Media and Mobile Positioning Data In Tourism Research: A Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For tourist destinations and tourists, the development of educational tourism can increase the communication and interaction between tourists and residents in different places [9,13,14], so that tourists can promote different races and cultures [5]. This means that the development of educational tourism can promote interpersonal interaction.…”
Section: Social Functionmentioning
confidence: 99%